Sheikh Mohammed Khal's method of writing the biography of the Prophet of Islam (pbuh) - Mohammed, Asst. Prof. Dr. Bahman Saleh (Sulaimani Journal for Humanities, 2023)
Sheikh Muhammad Al-Khal is one of the most prominent scholars in contemporary Kurdish history. He excelled in his field as a scholar, judge, and researcher in Islamic sciences. Distinguished by his extensive knowledge in jurisprudence and exegesis, he authored numerous works that contributed to the dissemination of Islamic knowledge. His methodology was based on returning to the original Islamic sources, primarily the Quran and the Sunnah, while emphasizing a new reading of these texts and avoiding the myths and fabrications that had accumulated over time, which had led society into ignorance and darkness. In this study, we aim to examine Sheikh Muhammad Al-Khal’s methodology in writing about the Prophet’s biography and how it adheres to a rigorous approach, distinguishing it from previous works, especially those written in Kurdish. We analyzed his approach to the biography, including his handling of the introduction, content, and conclusion, and all sections that reflect his unique style, to derive the methodology that dominated his writing of the Prophet’s biography.